Enteric Methane Emission from Sheep Fed with Rhodes Grass Hay (Chloris gayana) Alone or Supplemented with Dried Distillers’ Grains with Solubles - Gere, José Ignacio (2022)
Livestock systems based on subtropical and tropical pastures are characterized by the lowproductivity of livestock due to the poor nutritional value of the forage (low nitrogen concentrationand digestibility, and high fiber and lignin concentrations). These conditions lead to low productivityand, consequently, high absolute emissions of methane (CH4) per unit of product. Dry distilledgrains with solubles (DDGS) are the main by-product resulting from ethanol production, and theyare characterized by their high-energy fibrous and protein content, thus becoming an option forthe supplementation of low-quality forage. This research investigated the effects of dietary DDGSinclusion on dry matter digestibility (DMD) and enteric CH4 emission. Eight adult sheep of 64   8 kglive weight were used. The duration of the study was 54 days, divided into two periods (changeoverdesign), which comprised a 17-day pre-experimental period and 10 days for experimental datacollection. Animals were allocated to one of two treatments used: hay (H) as a control treatment,where animals were fed with Rhodes grass hay alone; and H + DDGS, where animals were fedwith H supplemented with DDGS. CH4 emissions were estimated using the sulfur hexafluoride(SF6) tracer technique. Diets containing DDGS increased DMI by 22% (p < 0.05) and reduced dailyCH4 emissions by 24% (g/d), the CH4 yield by 35% (g/kg DMI), and the average value of CH4energy per gross energy intake (Ym) by 44%, compared to the control treatment (p < 0.05). Theexperiment demonstrated that supplementation with DDGS in low-quality roughage reduced dailyCH4 emissions, yields, and Ym.